When to switch captions off? Exploring the effects of L2 proficiency and vocabulary knowledge on comprehension of captioned and uncaptioned TV - Pujadas, Geòrgia; Muñoz, Carmen (Studies in Second Language Learning and Teaching, 2024)
The extent to which L2 television is viewed by foreign language learners will depend on the degree to which it is understood. The addition of captions has been shown to support comprehension (e.g., Birulés-Muntané & Soto-Faraco, 2016; Montero-Perez, Peters, & Desmet, 2014), especially when proficiency is low (e.g., Lavaur & Bairstow, 2011). Yet, little is known about the extent to which captions benefit comprehension as L2 proficiency increases. This study seeks to investigate the effect of captions at different proficiency levels, and to identify the level at which captions cease to enhance comprehension. A total of 250 Catalan/Spanish university students, who had L2 English proficiency ranging from A1 to C2, viewed nine episodes of an English TV series with and without captions. Results showed that captioned viewing had a significant advantage over uncaptioned viewing in comprehension tests with multiple-choice and true-false items, and that learners with higher L2 proficiency and larger vocabulary performed better. While having access to captions increased the odds of a correct response independently of learners’ L2 proficiency and vocabulary knowledge, the additive benefits of captions were no longer significant at the C2 level, suggesting a threshold beyond which uncaptioned viewing does not negatively impact comprehension. Pedagogical implications are discussed.